The Interaction Between Phonological and Semantic Processing in Reading Chinese Characters - Dang, Min; Zhang, Rui; Wang, Xiaojuan; Yang, Jianfeng (Frontiers in Psychology, 2019)
The contemporary models of visual word recognition reached a consensus on a cooperative division of labor between phonological and semantic processing. We examine how reading is influenced by the interaction of two processing in Chinese character reading since the ideographic property of the Chinese writing system is perfectly suitable to address this issue. The current study investigated whether Chinese character reading requires the interaction between orthography-to-phonology consistency and semantic processing of the whole character (imageability, Experiment 1) or the semantic radical (transparency, Experiment 2). Experiment 1 showed a significant effect of the consistency and a marginal effect of the imageability, but no interaction between the two. Experiment 2 found a significant effect of the semantic transparency and its interaction with phonological consistency, where the transparent effect was significant for inconsistent characters but not for consistent ones. The current finding provided direct evidence of the interplay between phonological and semantic processing and shed light on the language-general reading model.